2021
DOI: 10.3390/nu13030996
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Transfer of Polyunsaturated Fatty Acids in Mother–Infant Dyads as Analyzed at Time of Delivery

Abstract: Polyunsaturated fatty acids (PUFAs) are essential for fetal development, and intrauterine transfer is the only supply of PUFAs to the fetus. The prevailing theory of gestational nutrient transfer is that certain nutrients (including PUFAs) may have prioritized transport across the placenta. Numerous studies have identified correlations between maternal and infant fatty acid concentrations; however, little is known about what role maternal PUFA status may play in differential intrauterine nutrient transfer. Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Median nutrient concentrations in maternal and cord blood at the time of delivery are shown in Tables 2 and 3, respectively. Consistently with previous findings, cord plasma PUFA concentrations were lower than maternal plasma PUFA concentrations in our cohort [27].…”
Section: Baseline Characteristicssupporting
confidence: 94%
See 1 more Smart Citation
“…Median nutrient concentrations in maternal and cord blood at the time of delivery are shown in Tables 2 and 3, respectively. Consistently with previous findings, cord plasma PUFA concentrations were lower than maternal plasma PUFA concentrations in our cohort [27].…”
Section: Baseline Characteristicssupporting
confidence: 94%
“…A total of 55 mother-infant pairs were enrolled in this study. Median maternal age was 30 years (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34); median birth corrected gestational age was 39.3 weeks (36.7-40). In terms of race/ethnic group, we found that 58.2% of mothers were White, 20% were Black or African American, 10.9% were Hispanic, 1.8% were Asian or Pacific Islander, and 9.1% identified as other or unknown.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…Maternal adipose tissue together with maternal dietary supply are crucial fetal sources of LC-PUFAs [ 16 ]. While in utero, the transference of nutrients across the placenta is the single source of nutrition, and the n-6 and n-3 PUFAs have to cross the placenta preferentially through fatty acid transporters [ 43 ]. FATP1 and FATP4 are the only transporters with acyl-CoA-synthetase activity that prevent PUFA efflux [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Omega-3 fatty acids play a positive role in maternal-infant health, but maternal consumption of omega-3 fatty acids is often inadequate. [72][73][74] Diets rich in omega-3 fatty acids may reduce the risk of hypertension and HF by improving left ventricular ejection fraction, restoring arterial compliance, influencing autonomic tone, and reducing electrical excitability in the plasma membrane. [75][76][77] What Is Known in SSA?…”
Section: Heart Failurementioning
confidence: 99%